2021
DOI: 10.1002/hrm.22064
|View full text |Cite
|
Sign up to set email alerts
|

Chief executive officer positive framing and employee ownership

Abstract: Employee ownership is an important governance tool used to encourage employee participation and enhance employee productivity, but we know little about what encourages employee ownership. This study investigates the influence of chief executive officer (CEO) positive framing in public speeches on employee ownership. We propose that CEO positive framing can increase employee ownership when employees internalize CEOs' positive beliefs about firms' accomplishments and prospects. Using a sample of 664 U.S. listed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 133 publications
0
4
0
Order By: Relevance
“…We also included employee ownership as a control variable because it may influence CEO dismissal (Hollandts, 2018), and measured it as the percentage of firm stocks jointly owned by all nonexecutive employees. Following J. Li, Shi, and Dasborough (2021), we collected the employee ownership data from the U.S. Department of Labor Form 5,500 filings, which provide information of the total amount of a firm's common and preferred stock held by nonexecutive employees in employee stock ownership plans each year.…”
Section: Methodsmentioning
confidence: 99%
“…We also included employee ownership as a control variable because it may influence CEO dismissal (Hollandts, 2018), and measured it as the percentage of firm stocks jointly owned by all nonexecutive employees. Following J. Li, Shi, and Dasborough (2021), we collected the employee ownership data from the U.S. Department of Labor Form 5,500 filings, which provide information of the total amount of a firm's common and preferred stock held by nonexecutive employees in employee stock ownership plans each year.…”
Section: Methodsmentioning
confidence: 99%
“…McClean and Collins (2019) show that a combination of high-commitment HR practices and CEO charismatic leadership could result in low voluntary employee turnover and high firm performance. The evidence of higher employee ownership, which itself is a tool to encourage employee participation and enhance productivity, in firms with optimistic CEOs in Li et al (2021) suggests that optimism belief of CEOs can spread to employees. Furthermore, the well documented overinvestment by optimistic CEOs (as in Malmendier & Tate, 2005) also leads to higher capital expenditure, investment in human capital, and consequently higher employment growth.…”
Section: Relevant Literature and Hypothesis Developmentmentioning
confidence: 99%
“…However, there is little attention on how CEO optimism affects firms' employment decision. An exception is the recent work on employee ownership by Li et al (2021) who show that employees are more likely to purchase stock of their firms when CEOs use positive words in their speeches.…”
Section: Relevant Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Independent variable. Employee ownership was measured as the percentage of a firm's total outstanding shares held by non-executive employees (Bova et al, 2014(Bova et al, , 2015Li et al, 2021;Wang et al, 2009). Our measure of employee ownership excluded managerial ownership, as prior studies have shown that managerial ownership can prevent firms from being targeted (Ambrose and Megginson, 1992;Ghosh and Ruland, 1998;Mikkelson and Partch, 1989;North, 2001;Song and Walkling, 1993), which differs from the effect of non-executive employee ownership.…”
Section: Variablesmentioning
confidence: 99%